Review of George Th. Mavrogordatos’, 1915: Ο εθνικός διχασμός [1915: The national schism] - Hatzis, Aristides N. (Historein, 2017)
George Th. Mavrogordatos. 1915: Ο εθνικός διχασμός [1915: The national schism]. Athens: Patakis, 2015. 343 pp.